Rainwater and fog harvesting from solar panels - I. Alazzam; K. Shatanawi; R. Al-Weshah (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Jordan is among the most water-scarce countries in the world. The scarcity of water resources in Jordan is driving the development and advances of non-conventional water techniques that enable integrated management of water resources in addressing water scarcity challenges and promoting sustainable water use. Water harvesting of rainwater and fog techniques is one of the viable solutions to mitigate the water scarcity effects in Jordan. This study aimed to evaluate the quantity of rainwater and fog collected through the utilization of solar panels, while also conducting a feasibility analysis on the economic and environmental aspects of employing solar panels for rainwater and fog harvesting in a solar farm situated in Jordan.METHODS: In the present study, an in-situ experiment is conducted to investigate rainwater and fog harvesting from solar panels' surfaces that are widely spread in Jordan. The solar farm situated in Hai Al Sahabah, south of Amman, Jordan, incorporates an experimental arrangement that involves the installation of gutters, pipes, and water tanks beneath two solar panel samples. These panels have a total area of 4 square meters and will be monitored for a duration of 60 days.FINDING: The results of the experiment show that the total quantity of the harvested rainwater using two solar panels was 444 liters ranging from 0.8 liters per day to 117.66 liters per day, and the total harvested fog quantity was 28 liters ranging from 0.25 liters per day to 9.75 liters per day. The multilinear regression technique was employed to establish a correlation between the amount of harvested water and the crucial factors of wind direction, wind speed, relative humidity, and temperature at the solar farm. The analysis of the findings revealed a significant relationship between these variables. These relationships can be generalized to provide an estimation for the quantity of rainwater and fog harvesting in other locations. The quantity of harvested rainwater was primarily influenced by wind speed and direction, the quantity of harvested fog was mainly affected by relative humidity and temperature. The current study aims to analyze and deliberate on the collected amounts of water obtained through rainwater and fog harvesting from solar panels. The viability of implementing the method of rainwater and fog harvesting from solar panels will be examined in terms of economic and environmental factors.CONCLUSIONS: The quantity of rainwater gathered in this research with just two solar panels shows great potential for widespread use as a supplementary water supply. This method of rainwater and fog harvesting can be effectively applied to solar power plants which are widely spread in Jordan for use in solar panel cleaning, agriculture, groundwater recharge, and reducing stormwater discharge to assess and manage the risk of environmental damage. Rainwater and fog harvesting systems offer a higher level of efficiency and cost-effectiveness compared to other methods, especially when seamlessly integrated into the infrastructure of solar power plants. The benefits of solar panels by producing clean energy are not negotiable but combining energy production with water harvesting in solar power plants would offer even more advantages in enhancing the global environmental situation.